Good Governance in the Era of Global Neoliberalism - Demmers, Jolle; Fernández Jilberto, Alex E.; Hogenboom, Barbara (Routledge Studies in the Modern World Economy, 2004)
This new collection critically examines the new global policy of 'good governance'. This catchphrase of aid policy and development thinking has been the subject of too little analysis to date. This book redresses the balance. It places the prefix 'good', and exactly what that means, under the microscope and examines the impact of neoliberal governance in a wide range of countries and territories, including Chile, Russia, Argentina and Indonesia.